2005
DOI: 10.1074/jbc.m501631200
|View full text |Cite
|
Sign up to set email alerts
|

Mind Bomb-2 Is an E3 Ligase for Notch Ligand

Abstract: The zebrafish gene, mind bomb (mib), encodes a protein that positively regulates of the Delta-mediated Notch signaling. It interacts with the intracellular domain of Delta to promote its ubiquitination and endocytosis. In our search for the mouse homologue of zebrafish mind bomb, we cloned two homologues in the mouse genome: a mouse orthologue (mouse mib1) and a paralogue, named mind bomb-2 (mib2), which is evolutionarily conserved from Drosophila to human. Both Mib1 and Mib2 have an E3 ubiquitin ligase activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
105
4
7

Year Published

2006
2006
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(119 citation statements)
references
References 39 publications
3
105
4
7
Order By: Relevance
“…Skeletrophin, and its paralogue, mind bomb (also reported as DIP-1 (Jin et al, 2002) or mind bomb-1 (Koo et al, 2005b), target the intracellular region of Notch ligands and mediates ligand-dependent Notch activation. Internalization of Notch ligands followed by ubiquitination by skeletrophin and mind bomb is critical for Notch signal transduction (Itoh et al, 2003;Koo et al, 2005a, b;Pitsouli and Delidakis, 2005;Takeuchi et al, 2005;Wang and Struhl, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Skeletrophin, and its paralogue, mind bomb (also reported as DIP-1 (Jin et al, 2002) or mind bomb-1 (Koo et al, 2005b), target the intracellular region of Notch ligands and mediates ligand-dependent Notch activation. Internalization of Notch ligands followed by ubiquitination by skeletrophin and mind bomb is critical for Notch signal transduction (Itoh et al, 2003;Koo et al, 2005a, b;Pitsouli and Delidakis, 2005;Takeuchi et al, 2005;Wang and Struhl, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the EGF receptor, mutation of multiple intracellular lysines within the kinase domain of the protein leads to an almost complete loss of EGF receptor ubiquitination but did not result in the decrease of its internalization rate (16). Regarding Notch ligands, it has been shown that the E3 ligase Mind Bomb 1 promotes ubiquitination and internalization of mammalian Dll1 (17). It has also been reported that to be active, Drosophila Delta has to traffic through a Neur/Mib-and epsin-dependent pathway, although the majority of Delta molecules traffic in a nonproductive manner through a different pathway, which is ubiquitination-dependent but epsin-independent and may lead to degradation (18).…”
Section: Several Authors Have Reported That Ubiquitination and Endocymentioning
confidence: 99%
“…1). Three of these colonies contained plasmids encoding the RING finger domain of Mib2, a protein that has previously been reported to have E3 ubiquitin ligase activity (37). Because of the recently identified role of the UPS in activity-dependent regulation of excitatory synaptic proteins (28 -30), we were interested in further characterizing whether Mib2 was a phosphorylation-dependent NR2B-interacting protein.…”
Section: Mib2 Interacts With the Nr2b Cytoplasmic Tail In A Fyn-depenmentioning
confidence: 99%
“…Mib2 Ubiquitinates NR2B in a Fyn Phosphorylation-dependent Manner-Mib2 is known to have intrinsic E3 ubiquitin ligase activity (37). To test whether the NR2B subunit is a substrate for Mib2, we performed ubiquitination assays.…”
Section: Mib2 Colocalizes With Nmdars Inmentioning
confidence: 99%